2000
DOI: 10.1889/1.1832878
|View full text |Cite
|
Sign up to set email alerts
|

53.1: 2.6 inch HDTV Panel Using CG Silicon

Abstract: inch HDTV panel has been developed on the CORNINNG 1737 glass substrate using low temperature CG Silicon (Continuous Grain Silicon). This time we have fabricated TFTs using CG Silicon which uses crystallization with metal catalyst (Ni) and the process to remove this catalyst from channel regions by gettering below 550[ o C].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…The solid lines represent the best fits to equation (3). The extracted densities of the oxide traps near the interface are presented in figure 7 for X-oriented and Yoriented devices with different front gate lengths.…”
Section: B Flicker Noise Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The solid lines represent the best fits to equation (3). The extracted densities of the oxide traps near the interface are presented in figure 7 for X-oriented and Yoriented devices with different front gate lengths.…”
Section: B Flicker Noise Analysismentioning
confidence: 99%
“…Many studies have demonstrated the ability of poly-Si based transistors to support a variety of functions beyond pixel switching, which has been the traditional role of TFTs in FPD applications [1]- [3]. High quality poly-Si microstructure is needed for the fabrication of high-quality poly-Si TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…The VL reference voltage determined by the MSBs charges up the video line through the pre-charge switch to one of 8 possible voltage levels. The table above summarizes the specifications of the 2" QVGA multi-format digital display we have designed and fabricated with a low-temperature Continuous Grain Silicon process [5,6]. This high performance TFT process is especially suitable for integrated digital drivers.…”
Section: Figure 7: Digital To Analogue Convertermentioning
confidence: 99%
“…Low-temperature polycrystalline silicon (LTPS) on glass have attracted considerable interest for large-area electronics including active-matrix liquid-crystal display (AMLCDs) [1], active-matrix organic light emitting diodes (AMOLEDs) [2], and system-onglass (SOG) [3] due to its high field-effect mobility, compared to amorphous silicon (a-Si).…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Sakamoto et al reported the successful fabrication of the a-Si:H TFTs on metal foil. [3] Since the melting points of SS foil is ~1400 ℃, which is similar to that of silicon (1412 ℃), it is possible to exploit the high temperature process to crystallize the amorphous silicon precursor. [6] To realize the top emission AMOLED back planes and CMOS (Complementary Metal-Oxide Semiconductor) circuits, Wagner et al crystallized a-Si on a spinon glass (SOG) / metal foil substrates at the temperature of 900 ℃ for 20s.…”
Section: Introductionmentioning
confidence: 99%